Preduodenal portal vein in association with midgut malrotation and duodenal web—triple anomaly? - Singal, Arbinder Kumar; Ramu, Chithra; Paul, Sarah; Matthai, John (Journal of pediatric surgery, 2009)
Preduodenal portal vein (PDPV) is a rare anomaly in which the portal vein passes anterior to the duodenum rather than posteriorly. Generally asymptomatic, PDPV may rarely cause duodenal obstruction or may coexist with other anomalies. We report a neonate who presented with duodenal obstruction and was found out to have 3 coexisting anomalies, each of which can lead to duodenal obstruction independently—PDPV, midgut malrotation, and duodenal web. A duodenoduodenostomy and a Ladd procedure were done, and the child recovered uneventfully. The mechanism of obstruction, interesting metabolic aberrations observed, outcome, and relevant literature are presented.